2012
DOI: 10.1210/jc.2012-1336
|View full text |Cite
|
Sign up to set email alerts
|

Abnormalities in Muscle Density and Muscle Function in Hypophosphatemic Rickets

Abstract: The present study suggests that muscle weakness is a clinical feature of HPR. Lower muscle quality and limb deformities contribute to this functional deficit.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
64
0
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 58 publications
(67 citation statements)
references
References 29 publications
2
64
0
1
Order By: Relevance
“…Children carriers of any of these mutations have soft bones (rickets), growth retardation, poor dental development, and elevated serum FGF23 levels [46]. It has been shown that accumulation of FGF23 is strongly associated with muscle function abnormalities in humans [47, 48].…”
Section: Human and Animal Bone-focused Knock-out “Models” Comprising mentioning
confidence: 99%
“…Children carriers of any of these mutations have soft bones (rickets), growth retardation, poor dental development, and elevated serum FGF23 levels [46]. It has been shown that accumulation of FGF23 is strongly associated with muscle function abnormalities in humans [47, 48].…”
Section: Human and Animal Bone-focused Knock-out “Models” Comprising mentioning
confidence: 99%
“…Adults with XLH are prone to pseudofractures and fractures due to a combination of osteomalacia and skeletal deformities resulting from rickets in childhood that expose long bones to abnormal biomechanical stress . In addition, many patients have early and accelerated osteoarthritis in weight‐bearing joints, lower limb deformities, acquired joint malalignment, enthesopathy, and muscle function deficits . These musculoskeletal abnormalities are prominent and debilitating features in adults with XLH that cause pain and stiffness, impairing mobility and physical function, and reducing health‐related quality of life …”
Section: Introductionmentioning
confidence: 99%
“…As 27 muscle force and bone mass are usually closely related, we hypothesized that muscle weakness in OI type I 28 could contribute to increase bone mass deficit in the lower extremities. 29 Objective: To assess the muscle-bone relationship in the lower extremities of children and adolescents with OI 30 type I. 31 Setting: The study was carried out in the outpatients department of a pediatric orthopedic hospital.…”
mentioning
confidence: 99%